From the Army to college transitioning from the service to higher education - Ventrone, Jillian 1973-; Karczewski, Paul 1981- (Rowman & Littlefield, 2015)
Making the transition from the military to higher education can be tricky. This guidebook will make the process easy, accessible, and understandable to any current or former member of the Army pursuing higher education while on active-duty or just leaving the service